Laser-assisted sintering molybdenum-manganese method ceramic metallization method
Through the laser-assisted sintering molybdenum-manganese ceramic metallization method, the problems of high sintering temperature of alumina ceramic and insufficient ceramic-metal binding force are solved, lower sintering temperature and higher binding strength are achieved, and the metallization quality and physical properties are improved.
Patent Information
- Application Number
- CN202411833610.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The problem of high metallization sintering temperature of alumina ceramics and insufficient bonding force of ceramic-metal cross-section.
The ceramic metallization method is adopted by laser-assisted sintering molybdenum-manganese method, including pretreatment of the ceramic substrate, preparation of metallized mixed powder and organic solvents, preparation of metallized slurry, and laser sintering treatment to reduce the sintering temperature and improve the ceramic-metal bonding strength.
It effectively reduces the sintering temperature, reduces the deformation and cracks of the ceramic matrix, and improves the metallization quality and the wear and tensile properties of the ceramic-metal composite.
Smart Images

Figure CN119552001A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic material processing, and in particular relates to a laser-assisted sintering molybdenum-manganese ceramic metallization method. Background Art
[0002] Metal-ceramic composites have shown extensive application potential in a variety of industries, including aerospace, automotive, mechanical, electronic, chemical, medical, energy, construction, military, and environmental engineering, with their excellent hardness, wear resistance, high temperature resistance, corrosion resistance, good thermal stability, excellent mechanical properties, electrical and thermal conductivity, low thermal expansion coefficient, biocompatibility, and environmental friendliness. These materials combine the toughness of metals with the rigidity of ceramics to provide a solution that can maintain stable performance in extreme environments. They also play an important role in improving product durability, efficiency, and safety, and have become an indispensable high-performance material in the development of modern industry and technology.
[0003] The connection problems between ceramics and metals are mainly caused by the differences in thermal expansion coefficient, wettability, brittleness and metallurgical compatibility between the two. These differences lead to residual stress, cracks and loose connections during the connection process. To solve these problems, researchers have developed a variety of connection technologies, including mechanical connection, adhesive connection, brazing connection, solid-phase diffusion connection, transient liquid phase connection, melting welding, self-propagating high-temperature synthesis connection and other methods. Each method has its applicable scenarios and limitations. With the advancement of technology, these connection methods are constantly improved and optimized to meet the growing demand of modern industry for ceramic-metal connections, ensure the strength, airtightness and high temperature resistance of the connection, thereby expanding the application field of ceramic materials and improving their application potential in high-end fields such as new energy vehicles, electronics and electrical, and semiconductor packaging.
[0004] Therefore, a new ceramic metallization technology needs to be developed in this field to effectively solve the above problems. Summary of the invention
[0005] The object of the present invention is to provide a laser-assisted sintering molybdenum-manganese ceramic metallization method, which can solve the problems of high sintering temperature of alumina ceramic metallization and insufficient bonding strength of ceramic-metal cross section.
[0006] To achieve the above object, the present invention provides a laser-assisted sintering molybdenum-manganese ceramic metallization method, comprising the following steps: S1, pre-treating the ceramic substrate; The 95 alumina ceramic substrate was polished with sandpaper and then ultrasonically cleaned in alcohol for 10-30 minutes; S2, preparing metallized mixed powder; S21. Weigh raw material powders according to the mass percentage of molybdenum powder 40-65%, manganese powder 10-25%, NiO 5-28%, SiO2 1-10%, Al2O3 1-10%, CuO 1-20%, and Fe2O3 1-5%; S22, dispersing the weighed raw material powder into anhydrous ethanol for ball milling; S23, ball milling and drying to obtain a metallized mixed powder; S3, preparing an organic solvent; Weigh 95-98% of terpineol and 2-5% of ethyl cellulose according to mass percentage, add the weighed ethyl cellulose into the terpineol under heating at 60-80° C. to heat and dissolve, thereby obtaining an organic solvent; S4, preparing metallization slurry; Add the metallization mixed powder to the organic solvent in a mass ratio of metallization mixed powder to organic solvent = 4:1, heat at 45-60°C and stir thoroughly to obtain a metallization slurry; S5, laser-assisted metallization sintering of alumina ceramic substrate; The metallized slurry prepared in step S4 is evenly coated on the 95 alumina ceramic substrate pretreated in step S1, and then dried, subjected to laser sintering treatment with different powers, and sintered to obtain a metallized ceramic product.
[0007] Preferably, in step S1, the mesh number of sandpaper used for sanding is 400-1000 mesh; and the volume fraction of ethanol in the alcohol is 60-80%.
[0008] Preferably, in step S2, the particle size D of molybdenum powder, manganese powder, NiO, Al2O3, CuO, and Fe2O3 is 50 All ≤1μm; SiO2 powder particle size is D 50 ≤0.5μm.
[0009] Preferably, in step S2, the ball milling time is 20-40 min, and the ball milling speed is 400-600 r / min; the temperature when drying the metallized mixed powder is 100-140° C., and the drying time is 30-50 min.
[0010] Preferably, in step S3, the time for heating and dissolving is 70 to 90 minutes.
[0011] Preferably, in step S4, the metallization mixed powder should be added while stirring during the preparation of the metallization slurry.
[0012] Preferably, in step S5, the metallization slurry is evenly coated manually using a brush; the drying temperature is 110-150° C., and the drying time is 40-70 min; and the laser used in the laser sintering process is a fiber continuous laser.
[0013] Preferably, the processing power of the laser is 150-380W; the sintering temperature of the 95 alumina ceramic substrate after laser sintering is controlled to be 1250-1380°C, and the sintering holding time is 60-100min.
[0014] The present invention adopts the above laser-assisted sintering molybdenum-manganese ceramic metallization method, and the beneficial effects are as follows: (1) The sintering temperature of the ceramic metallization method provided by the present invention after laser treatment is between 1250 and 1400°C, which is about 80°C lower than the current mainstream molybdenum-manganese metallization method, thereby reducing the negative effects of conventional high sintering temperatures on the ceramic matrix, such as deformation and cracking, and improving the metallization quality; (2) The metal layer of the present invention is partially diffused into the ceramic matrix after laser sintering pretreatment, so that the sintering temperature can be reduced during the subsequent high-temperature sintering, and the interface bonding strength between the metal layer and the ceramic matrix can be increased, thereby improving the physical properties of the ceramic-metal composite material such as wear resistance and tensile strength; (3) The present invention strictly controls the purity and particle size of the raw materials and performs preliminary ball milling on the metal molybdenum powder. These measures can effectively improve the activity of the powder. This can not only reduce the sintering temperature to a certain extent, but also enhance the permeability of the slurry, thereby achieving the formation of a thicker single-sintering metallization layer.
[0015] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a flow chart of an embodiment of a laser-assisted sintering molybdenum-manganese ceramic metallization method of the present invention; Figure 2 The cross-sectional microscopic morphology of a metallized ceramic product prepared in Example 1 of a laser-assisted sintering molybdenum-manganese ceramic metallization method of the present invention; wherein (a) is a microscopic morphology of a metallized ceramic sample sintered after 180W laser treatment at a scale of 10um; (b) is a partial enlarged view of the image of (a); Figure 3 The cross-sectional microscopic morphology of a metallized ceramic product prepared in Example 2 of a laser-assisted sintering molybdenum-manganese ceramic metallization method of the present invention; wherein (a) is a microscopic morphology of a metallized ceramic sample sintered after 230W laser treatment at a scale of 20um; (b) is a magnified view of a portion of the image (a); Figure 4The cross-sectional microscopic morphology of a metallized ceramic product prepared in Example 3 of a laser-assisted sintering molybdenum-manganese ceramic metallization method of the present invention; wherein (a) is a microscopic morphology of a metallized ceramic sample sintered after 280W laser treatment at a scale of 200um; (b) is a magnified view of a portion of the image (a); Figure 5 The cross-sectional microscopic morphology of a metallized ceramic product prepared in Example 1 of a laser-assisted sintering molybdenum-manganese ceramic metallization method of the present invention; wherein (a) is a microscopic morphology of a metallized ceramic sample obtained without laser treatment and sintering at a scale of 100 um; and (b) is a partially enlarged view of the image of (a). DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0018] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0019] like Figure 1 As shown, a laser-assisted sintering molybdenum-manganese ceramic metallization method comprises the following steps: S1. Pre-treating the ceramic substrate.
[0020] The 95 alumina ceramic substrate was polished with sandpaper and then placed in alcohol for ultrasonic cleaning for 10 to 30 minutes to increase the surface roughness of the alumina ceramic substrate and remove surface oil stains.
[0021] The mesh number of the sandpaper used for grinding is 400~1000. The volume fraction of ethanol in alcohol is 60~80%.
[0022] S2. Prepare metallized mixed powder.
[0023] S21. Weigh raw material powders according to the mass percentage of molybdenum powder 40-65%, manganese powder 10-25%, NiO 5-28%, SiO2 1-10%, Al2O3 1-10%, CuO 1-20%, and Fe2O3 1-5%.
[0024] Particle size D of molybdenum powder, manganese powder, NiO, Al2O3, CuO, Fe2O3 50 All ≤1μm. SiO2 powder particle size is D 50 ≤0.5μm, raw material powders are all analytical grade.
[0025] The addition of silicon dioxide (SiO2) can improve the wettability of metal powder to ceramics and improve its sealing performance. Alumina (Al2O3) helps to strengthen the connection between metal skeletons and improve the firmness of the seal. At the same time, the addition of activators CuO and Fe2O3 can increase the glass phase of the metallization slurry during high-temperature sintering, enhance the diffusion capacity of the metallization slurry, and promote high-temperature liquid phase sintering, which is conducive to the close bonding of the metallization layer and the ceramic substrate.
[0026] S22, dispersing the weighed raw material powder into anhydrous ethanol for ball milling. The ball milling time is 20-40 minutes, and the ball milling speed is 400-600 r / min.
[0027] S23, ball milling and drying to obtain metallized mixed powder. The drying temperature is 100-140°C and the drying time is 30-50 minutes.
[0028] S3. preparing an organic solvent.
[0029] According to the mass percentage, 95-98% of terpineol and 2-5% of ethyl cellulose are weighed, and the weighed ethyl cellulose is added to the terpineol under heating at 60-80° C. to heat and dissolve, thereby obtaining an organic solvent. The heating and dissolving time is 70-90 minutes.
[0030] S4. Prepare metallization slurry.
[0031] The metallization mixed powder is added to the organic solvent at a mass ratio of metallization mixed powder: organic solvent = 4:1, and heated at 45-60°C and stirred thoroughly to obtain the metallization slurry. The metallization mixed powder should be added while stirring during the preparation of the metallization slurry.
[0032] S5. Laser-assisted metallization sintering of alumina ceramic substrate.
[0033] The metallized slurry prepared in step S4 is evenly applied to the 95 alumina ceramic substrate pretreated in step S1 by hand using a brush, and then dried, sintered with lasers of different powers, and sintered to obtain a metallized ceramic product.
[0034] The drying temperature is 110~150℃ and the drying time is 40~70min.
[0035] The laser used in laser sintering is a fiber continuous laser with a processing power of 150~380w.
[0036] The sintering temperature of the 95 alumina ceramic substrate after laser sintering is controlled at 1250~1380℃, and the sintering holding time is 60~100min.
[0037] Embodiment 1 A laser-assisted sintering molybdenum-manganese ceramic metallization method comprises the following steps: S1. Pre-treating the ceramic substrate.
[0038] The prepared 95 alumina ceramic substrate was polished with 500-grit sandpaper for 15 minutes to increase the surface roughness of the ceramic plate. The polished 95 alumina ceramic substrate was placed in 85% alcohol and ultrasonically cleaned for 20 minutes to remove the oil stains on the surface.
[0039] S2. Prepare metallized mixed powder.
[0040] S21, weigh 50g of molybdenum powder, 15g of manganese powder, 6g of NiO, 5g of SiO2, 3g of Al2O3, 8g of CuO, and 2g of Fe2O3. The particle size of SiO2 powder is D 50 ≤0.5μm. Particle size of molybdenum powder, manganese powder, NiO, Al2O3, CuO, Fe2O3 50 All the raw material powders are ≤1μm, and all the raw material powders are analytical grade.
[0041] S22. Mix and dissolve the above raw material powders in anhydrous ethanol and ball-mill for 30 minutes at a rotation speed of 500 r / min.
[0042] S23. After ball milling, place in an oven and dry at 120° C. for 45 min to obtain a metallized mixed powder.
[0043] S3. preparing an organic solvent.
[0044] Weigh 100 g of terpineol in a beaker, then weigh 6 g of ethyl cellulose and add them to the terpineol while stirring at 70° C. Stop heating and stirring after the cellulose is completely dissolved.
[0045] S4. Prepare metallization slurry.
[0046] 10 g of the organic solvent prepared in step S3 was weighed in a beaker, and then 40 g of the metal mixed powder prepared in step S2 was weighed and added into the organic solvent while being heated at 55° C. and stirred to uniformly disperse the powder to obtain a metallization slurry.
[0047] S5. Laser-assisted metallization sintering of alumina ceramic substrate.
[0048] The metallization slurry obtained in step S4 is manually coated on the 95 alumina ceramic substrate degreased in step S1 using a brush, and then placed in an oven for drying at 120°C for 60 minutes. After drying, a continuous fiber laser is used to scan and sinter at a speed of 500 mm / s at a power of 180 W. The ceramic substrate coated with the metal slurry after laser sintering is sintered in a high-temperature tube furnace at a temperature of 1280°C for 90 minutes to obtain a metallized ceramic product.
[0049] Embodiment 2 A laser-assisted sintering molybdenum-manganese ceramic metallization method comprises the following steps: S1. Pre-treating the ceramic substrate.
[0050] The prepared 95 alumina ceramic substrate was polished for 15 minutes using 500-grit sandpaper to increase the surface roughness of the ceramic plate. The polished 95 alumina ceramic substrate was then ultrasonically cleaned in 85% alcohol for 20 minutes to remove the oil on the surface.
[0051] S2. Prepare metallized mixed powder.
[0052] S21, weigh 50g of molybdenum powder, 15g of manganese powder, 6g of NiO, 5g of SiO2, 3g of Al2O3, 8g of CuO, and 2g of Fe2O3. The particle size of SiO2 powder is D 50 ≤0.5μm. Particle size of molybdenum powder, manganese powder, NiO, Al2O3, CuO, Fe2O3 50 All the raw material powders are ≤1μm, and all the raw material powders are analytical grade.
[0053] S22. Mix and dissolve the above raw material powders in anhydrous ethanol and ball-mill for 30 minutes at a rotation speed of 500 r / min.
[0054] S23. After ball milling, the mixture is placed in an oven and dried at 120° C. for 45 min to obtain a metallized mixed powder.
[0055] S3. preparing an organic solvent.
[0056] Weigh 100 g of terpineol in a beaker, then weigh 6 g of ethyl cellulose and add them to the terpineol while stirring at 70° C. Stop heating and stirring after the cellulose is completely dissolved.
[0057] S4. Prepare metallization slurry.
[0058] 10 g of the organic solvent prepared in step S3 was weighed in a beaker, and then 40 g of the metal mixed powder prepared in step S2 was weighed and added into the organic solvent while being heated at 55° C. and stirred to uniformly disperse the powder to obtain a metallization slurry.
[0059] S5. Laser-assisted metallization sintering of alumina ceramic substrate.
[0060] The metallization slurry obtained in step S4 is manually coated on the 95 alumina ceramic substrate degreased in step S1 using a brush, and then placed in an oven for drying at 120°C for 60 minutes. After drying, a continuous fiber laser is used to scan and sinter at a speed of 500 mm / s at a power of 230w. The ceramic substrate coated with the metal slurry after laser sintering is sintered in a high-temperature tube furnace at a temperature of 1280°C for 90 minutes to obtain a metallized ceramic product.
[0061] Embodiment 3 A laser-assisted sintering molybdenum-manganese ceramic metallization method comprises the following steps: S1. Pre-treating the ceramic substrate.
[0062] The prepared 95 alumina ceramic substrate was polished for 15 minutes using 500-grit sandpaper to increase the surface roughness of the ceramic plate. The polished 95 alumina ceramic substrate was then ultrasonically cleaned in 85% alcohol for 20 minutes to remove the oil on the surface.
[0063] S2. Prepare metallized mixed powder.
[0064] S21, weigh 50g of molybdenum powder, 15g of manganese powder, 6g of NiO, 5g of SiO2, 3g of Al2O3, 8g of CuO, and 2g of Fe2O3. The particle size of SiO2 powder is D 50 ≤0.5μm. Particle size of molybdenum powder, manganese powder, NiO, Al2O3, CuO, Fe2O3 50 All the raw material powders are ≤1μm, and all the raw material powders are analytical grade.
[0065] S22. Mix and dissolve the above raw material powders in anhydrous ethanol and ball-mill for 30 minutes at a rotation speed of 500 r / min.
[0066] S23. After ball milling, the mixture is placed in an oven and dried at 120° C. for 45 min to obtain a metallized mixed powder.
[0067] S3. preparing an organic solvent.
[0068] Weigh 100 g of terpineol in a beaker, then weigh 6 g of ethyl cellulose and add them to the terpineol while stirring at 70° C. Stop heating and stirring after the cellulose is completely dissolved.
[0069] S4. Prepare metallization slurry.
[0070] 10 g of the organic solvent prepared in step S3 was weighed in a beaker, and then 40 g of the metal mixed powder prepared in step S2 was weighed and added into the organic solvent while being heated at 55° C. and stirred to uniformly disperse the powder to obtain a metallization slurry.
[0071] S5. Laser-assisted metallization sintering of alumina ceramic substrate.
[0072] The metallization slurry obtained in step S4 is manually coated on the 95 alumina ceramic substrate degreased in step S1 using a brush, and then placed in an oven for drying at 120°C for 60 minutes. After drying, a continuous fiber laser is used to scan and sinter at a speed of 500 mm / s at a power of 280w. The ceramic substrate coated with the metal slurry after laser sintering is sintered in a high-temperature tube furnace at a temperature of 1280°C for 90 minutes to obtain a metallized ceramic product.
[0073] Comparative Example 1 A method for metallizing alumina ceramics comprises the following steps: S1. Pre-treating the ceramic substrate.
[0074] The prepared 95 alumina ceramic substrate was polished for 15 minutes using 500-grit sandpaper to increase the surface roughness of the ceramic plate. The polished 95 alumina ceramic substrate was then ultrasonically cleaned in 85% alcohol for 20 minutes to remove the oil on the surface.
[0075] S2. Prepare metallized mixed powder.
[0076] S21, weigh 50g of molybdenum powder, 15g of manganese powder, 6g of NiO, 5g of SiO2, 3g of Al2O3, 8g of CuO, and 2g of Fe2O3. The particle size of SiO2 powder is D 50 ≤0.5μm. Particle size of molybdenum powder, manganese powder, NiO, Al2O3, CuO, Fe2O3 50 All the raw material powders are ≤1μm, and all the raw material powders are analytical grade.
[0077] S22. Mix and dissolve the above raw material powders in anhydrous ethanol and ball-mill for 30 minutes at a rotation speed of 500 r / min.
[0078] S23. After ball milling, the mixture is placed in an oven and dried at 120° C. for 45 min to obtain a metallized mixed powder.
[0079] S3. preparing an organic solvent.
[0080] Weigh 100 g of terpineol in a beaker, then weigh 6 g of ethyl cellulose and add them to the terpineol while stirring at 70° C. Stop heating and stirring after the cellulose is completely dissolved.
[0081] S4. Prepare metallization slurry.
[0082] 10 g of the organic solvent prepared in step S3 was weighed in a beaker, and then 40 g of the metal mixed powder prepared in step S2 was weighed and added into the organic solvent while being heated at 55° C. and stirred to uniformly disperse the powder to obtain a metallization slurry.
[0083] S5. Direct metallization sintering of alumina ceramic substrate The metallization slurry obtained in step S4 is manually coated on the 95 alumina ceramic substrate degreased in step S1 using a brush, and then placed in an oven for drying at 120°C for 60 minutes. After drying, the ceramic substrate coated with the metal slurry is sintered in a high-temperature tube furnace at 1280°C for 90 minutes to obtain a metallized ceramic product.
[0084] The metallized ceramic products prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were tested.
[0085] like Figure 2 , Figure 3 , Figure 4 , Figure 5 As shown in FIG. 1 , the upper half of the layers are all metal layers, and the lower half are all alumina ceramic layers. It can be seen that in the cross-sectional microscopic SEM images of the metallized ceramic products prepared in Example 1, Example 2, and Example 3 after laser scanning, as shown in FIG. Figure 2 Middle (a), Figure 2 Middle (b), Figure 3 Middle (a), Figure 3 Middle (b), Figure 4 Middle (a), Figure 4 As shown in (b), the metal layer is relatively uniform and closely bonded to the ceramic substrate. Figure 5 Middle (a), Figure 5 As shown in (b), there is an obvious gap between the metal layer and the ceramic substrate, that is, the bonding between the two is poor. Therefore, it can be considered that laser-assisted processing has a certain positive effect on the ceramic metallization performance.
[0086] Therefore, the present invention adopts the above-mentioned laser-assisted sintering molybdenum-manganese method for ceramic metallization to solve the problems of high sintering temperature of alumina ceramic metallization and insufficient bonding strength between ceramic and metal sections.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A laser-assisted sintering molybdenum-manganese ceramic metallization method, characterized in that: The following steps are involved: S1, pre-treating the ceramic substrate; The 95 alumina ceramic substrate was polished with sandpaper and then ultrasonically cleaned in alcohol for 10-30 minutes; S2, preparing metallized mixed powder; S21. Weigh raw material powders according to the mass percentage of molybdenum powder 40-65%, manganese powder 10-25%, NiO 5-28%, SiO2 1-10%, Al2O3 1-10%, CuO 1-20%, and Fe2O3 1-5%; S22, dispersing the weighed raw material powder into anhydrous ethanol for ball milling; S23, ball milling and drying to obtain a metallized mixed powder; S3, preparing an organic solvent; Weigh 95-98% of terpineol and 2-5% of ethyl cellulose according to mass percentage, add the weighed ethyl cellulose into the terpineol under heating at 60-80° C. to heat and dissolve, thereby obtaining an organic solvent; S4, preparing metallization slurry; Add the metallization mixed powder to the organic solvent in a mass ratio of metallization mixed powder to organic solvent = 4:1, heat at 45-60°C and stir thoroughly to obtain a metallization slurry; S5, laser-assisted metallization sintering of alumina ceramic substrate; The metallized slurry prepared in step S4 is evenly coated on the 95 alumina ceramic substrate pretreated in step S1, and then dried, subjected to laser sintering treatment with different powers, and sintered to obtain a metallized ceramic product.
2. The laser-assisted sintering molybdenum-manganese ceramic metallization method according to claim 1, characterized in that: In step S1, the mesh number of the sandpaper used for sanding is 400-1000 mesh; the volume fraction of ethanol in the alcohol is 60-80%.
3. The laser-assisted sintering molybdenum-manganese ceramic metallization method according to claim 1, characterized in that: In step S2, the particle size D of molybdenum powder, manganese powder, NiO, Al2O3, CuO, and Fe2O3 is 50 All ≤1μm; SiO2 powder particle size is D 50 ≤0.5μm.
4. The laser-assisted sintering molybdenum-manganese ceramic metallization method according to claim 1, characterized in that: In step S2, the ball milling time is 20-40 min, and the ball milling speed is 400-600 r / min; the temperature when drying the metallized mixed powder is 100-140° C., and the drying time is 30-50 min.
5. The laser-assisted sintering molybdenum-manganese ceramic metallization method according to claim 1, characterized in that: In step S3, the heating and dissolving time is 70 to 90 minutes.
6. The laser-assisted sintering molybdenum-manganese ceramic metallization method according to claim 1, characterized in that: In step S4, the metallization mixed powder should be added while stirring during the preparation of the metallization slurry.
7. The laser-assisted sintering molybdenum-manganese ceramic metallization method according to claim 1, characterized in that: In step S5, the metallization slurry is evenly coated manually using a brush; the drying temperature is 110-150° C., and the drying time is 40-70 min; the laser used in the laser sintering process is a fiber continuous laser.
8. The laser-assisted sintering molybdenum-manganese ceramic metallization method according to claim 7, characterized in that: The processing power of the laser is 150~380w; the sintering temperature of the 95 alumina ceramic substrate after laser sintering is controlled to be 1250~1380℃, and the sintering holding time is 60~100min.
Citation Information
Patent Citations
Ceramic-based circuit board and preparation method thereof
CN104822223A
Silicon nitride ceramic surface metallization method
CN111269028A
Ultrahigh-purity aluminum oxide ceramic metallization method
CN111548193A
Preparation method of ceramic / metal composite material
CN117263710A
METHOD OF METALLIZING CERAMICS
RU2019106569A